Non-Technical Skills According to the Preferences for Small Medium Industries in Facing Revolution Industry 4.0: An Application of the Fuzzy Delphi Technique - Sallehudin Ayub; Alias Masek; Saiful Hadi Masran (Research and Innovation in Technical and Vocational Education and Training, 2025)
Small and Medium Enterprise (SME) sector plays a crucial role in boosting the country’s economy. Despite their potentially small size, their impact on economic growth, job creation, and local community development is highly significant. However, SMEs often face challenges related to a lack of non-technical skills among their workforce. Therefore, this study aims to determine the priority of non-technical skills for SMEs. The study employs a two-phase research design, consisting of (1) a Systematic Literature Review (SLR) and (2) the Fuzzy Delphi Method (FDM). In Phase 1, the researcher applies the PRISMA model as a guide to conducting an SLR on 129 articles identified through the Google Scholar database. The results of the systematic literature review indicate the existence of 14 non-technical skills for SMEs in the context of Industry 4.0. The FDM is utilized to obtain expert consensus on these skills. Ten SME owners in the Batu Pahat area are selected as study participants. The FDM analysis reveals that the expert panel agrees that all the non-technical skills identified in previous studies are crucial for SMEs in Industry 4.0. Non-technical skills are prioritized for SMEs based on expert opinions. Creativity is identified as the highest-priority non-technical skill according to the SME owners’ perspectives. The implications of this study serve as exposure and guidance for employers, employees, and the community regarding the importance of non-technical skills for SMEs in the current Industry 4.0 landscape.